Deceased patients with chronic kidney disease. Characteristics and causes in Cuba during 2011-2016 - Maria del Carmen Marin Prada; Francisco Gutiérrez García; Miguel Ángel Martínez Morales; Carlos Antonio Rodríguez García; Guillermo Guerra Bustillo; Jorge F. Pérez-Oliva Díaz (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Chronic kidney disease (CKD) has increased at an alarming rate worldwide over the last two decades. Although mortality due to CKD has registered stable behavior in Cuba, its prevalence and incidence are showing higher rates. Objective: To describe the main demographic features of deceased patients with CKD in Cuba, the causes of death and other variables during the period 2011-2016. Material and Methods: A descriptive cross-sectional study was conducted.  The study universe included all deceased patients in Cuba during the period mentioned. CKD was listed on their death certificates as one of the causes of death. The information used was obtained from the mortality database available on the National Directorate of Medical Records and Health Statistics of the Cuban Ministry of Public Health. Data was processed using SPSS version 22.0. Absolute and relative frequencies were calculated. Results: The global frequency of deceased patients showed a steady increase.  Havana was the city that presented the highest percentage (23,6 %).  Nonetheless, the rest of the cities showed an increased frequency rate. The median age was 70 years. The male gender prevailed over the female one as well as white ethnicity and the 80 years and over age group. Regarding the cause of death, the highest percentages corresponded to hypertensive kidney disease and Diabetes Mellitus. Conclusions: Most of the deceased patients with CKD are male, white and at advanced ages.  The main causes of death are hypertensive disease and Diabetes Mellitus.